2019
DOI: 10.1108/ijm-09-2017-0243
|View full text |Cite
|
Sign up to set email alerts
|

Beyond retirement: who stays at work after the standard age of retirement?

Abstract: Purpose Drawing on a unique combination of longitudinal administrative data and a postal survey, the purpose of this paper is to identify the socio-economic factors and individual characteristics that affect senior citizens’ decision to continue working on the Swedish labour market after the standard retirement age. Design/methodology/approach By using standard econometric techniques (multinomial logit model) on a large representative sample of 20,000 senior citizens residing in Sweden, the auhtors analyse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 30 publications
2
33
1
2
Order By: Relevance
“…The results of these studies suggest that working conditions and psychological work environment are important determinants of working beyond the state pension age. Retrospective data ( 11 ) show that job control and work autonomy are associated with working after age 65 in Sweden, while having a physically or psychologically demanding job reduces the likelihood of working beyond this age. Similarly, using cross-sectional data from 16 European countries, the SHARE study reported that psychosocial working conditions were generally better among those working beyond retirement compared to previous conditions among those retired.…”
mentioning
confidence: 99%
“…The results of these studies suggest that working conditions and psychological work environment are important determinants of working beyond the state pension age. Retrospective data ( 11 ) show that job control and work autonomy are associated with working after age 65 in Sweden, while having a physically or psychologically demanding job reduces the likelihood of working beyond this age. Similarly, using cross-sectional data from 16 European countries, the SHARE study reported that psychosocial working conditions were generally better among those working beyond retirement compared to previous conditions among those retired.…”
mentioning
confidence: 99%
“…In addition, it should be noted that the Nagelkerke R Squares were quite low (see Tables 3 and 4 ), indicating that besides prior SA, DP, and the sociodemographic covariates, there were other factors that can explain work participation past the age of 65 than those accounted for in this model. Such factors could, e.g., be influence by significant others [ 15 , 55 ], the employer [ 11 ], societal and group norms regarding retirement [ 56 ], work environment [ 22 , 51 ], motivation to continue in paid work [ 22 ], personality [ 57 ], type of morbidity, as well as duration, rate (part- or full-time), and number of SA and DP spells. Moreover, one limitation is the possible overlap between SA and DP, which might affect the results of the analysis in which SA and DP were separate exposure variables.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ageing process in EU countries, there has been a growing interest in active ageing and even in what determines working beyond retirement (Anxo et al, 2012(Anxo et al, , 2019. However, in ageing societies, the heirs will be increasingly older; therefore, we should expect that more people would leave the labour force when receiving an inheritance.…”
Section: Ijmmentioning
confidence: 99%